Fungsi Fisik, Status Gisi dan Komposisi Tubuh Mahasiswa Fakultas Kedokteran Universitas Wijaya Kusuma Surabaya - Budhi Setiawan; Inggit Andhika; Ika Praningtias; Ernawati Ernawati; Herni Suprapti (HANG TUAH MEDICAL JOURNAL, 2021)
ABSTRACTBackground: Hand grip is an indicator that can be used to evaluate nutritional status and also physical strength. Handgripstrength test is one of thecommonassessments that may be appliedeasily and quickly in various health care services to obtain accurate results.Method: Cross-sectional technique was implemented involving one hundred and forty medical students divided into two groups. Analysis in the first group (n =78) was conducted to measure the strength of the hand alongwith body mass index (BMI) and mid-upper arm circumference(MUAC). While the second group (n = 62) measurement includedthe handgripstrength andbody composition (fat and water composition and lean mass).Nutritionalstatus measurement wasappliedusing digital scales and height gauges,while Medline tape for MUAC evaluation. Handgripstrength was assessedusing a handgrip dynamometer while body composition was analyzed with handheld bio-impedance analysis (BIA).Result: The values of BMI,MUACwater and fat composition showed higher values (p<0.05) in men except lean mass. Correlations were shown between handgrip strength with BMI (r=0.48; α<0.05), LILA (r=0.43; α<0.05), fat proportion (r=0.73; α<0.05), and lean mass (r=-0.37; α<0.05).Conclusion: Male students demonstratedhigher BMI, MUAC, and body fat composition values than female students. Handgripstrength increased consistently along with the increment ofbody mass index (BMI), mid-upper arm circumference (MUAC), and body fat proportions but describeda negative correlation with lean mass.